Pengaruh Pengungkapan ESG, Ukuran Perusahaan, Leverage terhadap Tax Avoidance pada Perusahaan Sektor Energi yang terdaftar di BEI Tahun 2021-2025 - Salma Salsabila; Arry Irawan; Iyeh Supriatna; Annas Rahmat Ramadhani (Indonesian Accounting Literacy Journal, 2026)
This study aims to determine the effect of ESG disclosure, Company Size and Leverage on Tax Avoidance. The sample includes energy sector companies listed on the IDX for the 2021-2025 period, selected using a purposive sampling technique. The independent variables are ESG Disclosure measured by GRI 2021, Company Size measured by the natural logarithm of total assets, and Leverage measured by the Debt-to-Asset Ratio. The dependent variable used is Tax Avoidance measured by Book-Tax Difference. Secondary data from annual reports and sustainability reports were analyzed using panel data regression via EViews 13. Result indicates that ESG Disclosure does not affect Tax Avoidance, whereas Company Size and Leverage have a negative effect, simultaneously all variables significantly affect Tax Avoidance. This study theoretically contributes by expanding empirical evidence on Agency and Legitimacy theories. A key limitation is the low Adjusted R-squared, suggesting future studies incorporate other variables.